2012
DOI: 10.1089/neu.2011.2171
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Levels of High-Mobility Group Box 1 and Cytochrome C Predict Outcome after Pediatric Traumatic Brain Injury

Abstract: High-mobility group box 1 (HMGB1) is a ubiquitous nuclear protein that is passively released from damaged and necrotic cells, and actively released from immune cells. In contrast, cytochrome c is released from mitochondria in apoptotic cells, and is considered a reliable biomarker of apoptosis. Thus, HMGB1 and cytochrome c may in part reflect the degree of necrosis and apoptosis present after traumatic brain injury (TBI), where both are felt to contribute to cell death and neurological morbidity. Ventricular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 50 publications
(50 reference statements)
1
67
1
Order By: Relevance
“…Its elevation is associated with the severity of brain damage following TBI [28]. Previous studies revealed that HMGB1 was translocated from the nucleus to the cytoplasm, and was released out of necrotic cells at early stages following TBI [9, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Its elevation is associated with the severity of brain damage following TBI [28]. Previous studies revealed that HMGB1 was translocated from the nucleus to the cytoplasm, and was released out of necrotic cells at early stages following TBI [9, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Alicia and colleagues demonstrated that concentrations of HMGB1 are elevated in Cerebrospinal fluid (CSF) after trauma, and furthermore, these were separately related to poor outcomes [23]. They proposed that increased CSF HMGB1 is separately related to 6-month Glasgow Coma Scale (GOS) score 1 -3 which reflects a poor outcome.…”
Section: Hmgb1 As a Biomarkermentioning
confidence: 99%
“…Studies have shown that damage induced by trauma or ischemia can evoke HMGB1 secretion from necrotic tissue which may provide danger signal that alerts the immune system to the existence of injured cells [23] [26]. The traumatic events leading to the secretion of HMGB1 into the CSF also initiate the secretion of other DAMP into the CSF with successive activation of the innate immune response [25].…”
Section: Mechanisms Of Secretion Of Hmgb1mentioning
confidence: 99%
“…This injury-induced excess of catecholamine also lends itself to hypertension, abnormal heart variability and neurological deficits (44,90,112). More recent clinical studies implicate the production and release of inflammatory mediators, including HMGB1 (8,49,75,122). Though organ failure scoring systems, present clinical markers and single cytokine estimates have failed to predict the onset of organ dysfunction in the clinical setting, patterns of early circulating trauma markers such as HMGB1 may serve to guide and streamline damage control following TBI.…”
Section: Hmgb1 and Traumatic Brain Injurymentioning
confidence: 99%
“…Some clinical studies of mechanical trauma in the absence of head injury fail to find a correlation between HMGB1 levels in plasma and measures of morbidity (88). However, other studies which included patients with trauma to the head suggest that the release of HMGB1 is predictive of both mortality and neurological dysfunction in adult and pediatric patients (8,28,42). The presence of the increased HMGB1 levels in both plasma and cerebrospinal fluid may ultimately reflect release from damaged and dying cells in the brain.…”
Section: Hmgb1 and Traumatic Brain Injurymentioning
confidence: 99%